Analysis Management Source Power Man on Lavanda Karawang Brownies - Widi Kusnia,; Uus Mohammad Darul Fadli,; Ery Rosmawati, (Research in Management of Technology and Business, 2024)
The food industry in Indonesia is an important sector for economic growth in this country. Now, food is not only a basic human need, but has become part of a new lifestyle in society which therefore requires good and effective human resource management. This research uses a qualitative descriptive approach analysis method, which was carried out at Lavanda Brownis Karawang located on Jalan Perumnas block A. Data collection used primary data through interviews with shop owners, managers and marketing staff, as well as using content analysis. This research aims to analyze how the HR management system is based on recruitment, selection, training, development, job placement, assessment, promotion, sanctions and rewards, and to find out the obstacles in managing HR, as well as analyzing strategies to improve HR management. The results of this research show that there is still minimal implementation of HR management because there are still employees who do not comply with Production Operational Standards, and there are no assessments carried out regularly. Thus, the implementation of this HR management system is expected to create a better and more effective organization. The obstacles for shops are the difficulty in keeping up with the latest technological developments to increase the competitiveness of their products due to limited human resources, as well as the basic salary which is still below the minimum wage standard. Apart from that, strategies for selecting workers with high levels of employee responsibility can include changing targets, adjusting budgets, or utilizing different resources. Therefore, it is recommended that regular work assessments be made so that it can be a work motivation for employees by adding rewards so that employees feel well-being in the shop.